Constitutive Expression of Functionally Active Protease-Activated Receptors 1 and 2 in Human Conjunctival Epithelial Cells (Hindawi Limited, 2006)
Protease-activated receptors (PARs) are G-protein-coupled receptors which initiate inflammatory responses when activated by specific serine proteases. This study was conducted to examine whether human conjunctival epithelial cells (HCECs) express functionally active PAR1 and PAR2 using Chang conjunctival epithelial cells as in vitro model. We performed RT-PCR and immunofluorescence analyses to determine the expression of PAR1 and PAR2, and monitored the production of IL-6 after activating HCECs with PAR1 activating agents (thrombin or TFLLRN) or PAR2 activating agents (tryptase, trypsin, or SLIGKV). The results show that HCECs constitutively express PAR1 and PAR2 mRNA and proteins, and produce significant amounts of IL-6 when incubated with specific PAR-activating enzymes or agonist peptides. Thrombin- and tryptase-induced HCEC activation was blocked by PAR1 and PAR2 neutralizing antibodies, respectively, and by specific enzyme inhibitors. The constitutive expression of PAR1 and PAR2, and their activation by thrombin and tryptase, respectively, may have important implications in ocular inflammation.